Effects of Varying Levels of Dietary Protein on Growth and Reproductive Potential in Barilius bakeri - Antony, Jomol; Natarajan, p (Fishery Technology, 2025)
A 90 day experiment was conducted to observe the influence of varying levels of dietary protein on the growth and reproductive potential of Barilius bakeri. Diets were prepared with fish meal as the single source of protein. A total of twelve fishes weighing 1.6 Â± 0.2 g were stocked in glass tanks in triplicate for each of the treatment. Fishes were fed with 20, 30, 40 and 50% crude protein, twice daily. There was no significant weight increment between the different protein groups. Gonadosomatic index was significantly higher (p<0.05) for 30% and lowest for 20% group. Fecundity was highest for 30% (p<0.05) and least for 20%. For Barilius bakeri, a dietary protein level between 30 and 40% was found to be optimum with regard to growth and reproduction.